Efforts to Increase Legal Awareness in Preventing Narcotics Crimes Among Students - salim; Mela Novita Rizki; Chairus Suriyati; Junaidi Lubis (Outline Publisher, 2024)
This study aims to analyze the level of legal awareness of students and the effectiveness of various prevention programs that have been implemented. Using a qualitative approach with descriptive methods, data were collected through interviews, observations, and literature studies. The results of the study indicate that the majority of students do not understand the legal regulations related to narcotics, making them vulnerable to abuse. Interactive educational methods, such as legal case simulations and group discussions, have proven to be more effective than conventional lectures. Other factors contributing to low legal awareness are the lack of educators who have a deep understanding of narcotics law and weak family involvement in prevention. Schools that implement a community-based approach and strict supervision show more positive results in reducing drug abuse rates. This study recommends the integration of legal education into the school curriculum, training for teachers, and optimizing the role of digital media in disseminating information. With a comprehensive and sustainable approach, it is hoped that students' legal awareness will increase, so that drug abuse rates can be significantly reduced.